The S-shaped association between dietary caffeine intake and severe headache or migraine: a cross-sectional study based on NHANES - Liao, Zhiqiang; Lin, Aiqing; Zeng, Junjian; Zou, Yu; Chen, YiXun; Liu, Zhonghua; Zhou, Zhidong (Frontiers in Neurology, 2025)
Background and purposeSevere headache or migraine is a highly prevalent neurological disorder that significantly impacts the daily lives of those affected. Currently, there remains a debate regarding the relationship between daily caffeine intake and severe headache or migraine. This study aims to determine the relationship between caffeine intake and severe headache or migraine to inform dietary interventions.Materials and methodsThe study utilized data from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2004, involving a total of 5,234 participants aged 20–49 years. A multivariable logistic regression model was employed to examine the relationship between dietary caffeine intake and severe headache or migraine. A restricted cubic spline (RCS) regression model was used to explore potential dose–response relationships. A smoothed two-piece logistic regression model was applied to identify threshold associations between dietary caffeine intake and severe headache or migraine. Subgroup regression analyses were conducted to investigate whether the impact of dietary caffeine intake on severe headache or migraine varied among different subgroups.ResultsAmong the 5,234 participants, 26.69% (1,397/5234) had severe headache or migraine. Compared to individuals with lower caffeine intake (quartile [Q]1, ≤1.81 mg/d), those with higher caffeine intake in Q2 (1.81–45.48 mg/d), Q3 (45.48–125.95 mg/d), and Q4 (≥125.95 mg/d) had adjusted odds ratios for severe headache or migraine of 1.1487 (95% confidence interval [CI]: 0.9532–1.3845, p = 0.1454), 1.4370 (95% CI: 1.1921–1.7335, p = 0.001), and 1.5642 (95% CI: 1.2842–1.9067, p < 0.001), respectively. The relationship between dietary caffeine intake and severe headache or migraine in U.S. adults exhibits an S-shaped pattern, with a turning point at approximately 97.5 mg/d.ConclusionThese results suggest an S-shaped association between dietary caffeine intake and severe headache or migraine. Individuals who routinely consume caffeine in their diet should be vigilant about the risk of experiencing severe headaches or migraines.